Obstacles In The Process Behind The Legal Certificate Of Land Through The Binding Agreement Of Buying - Danita Adriani (IHSA Institute, 2020)
Assignment requirements sets in Article 37 paragraph 1 of Government Regulation No. 24 of 1997 on concerning land registration. From the practice oh the transfer of land rights, people don’t always make the payment in cash but also usually done in installments. To protects the buyer has paid the installments due under the name can't be done then the parties often bridged with make an accessoir agreement like purchase agreement , deed District Land Office of Tulungagung. At the District Land Office of Tulungagung found many local people are experiencing a lot of obstacles in process to change of name in the certificate of land rights with an accessoir agreement like purchase agreement neither made before a notary or under hanf.